150 Spinal Pelvic Radiographic Thresholds for Regional Lumbar Disability are Age Dependent: Analysis of Multicenter Database of 833 Patients. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Scheer, Justin K.; Smith, Justin S.; Lafage, Virginie; Shaffrey, Christopher I.; Lafage, Renaud; Klineberg, Eric; Gupta, Munish; Hostin, Richard A.; Kebaish, Khaled; Bess, Shay; Schwab, Frank; Ames, Christopher P.
Abstract: INTRODUCTION: The sagittal plane is the primary driver of disability in patients with adult spinal deformity (ASD), and spinopelvic radiographic thresholds have been established for pelvic tilt (PT), pelvic incidence (PI) and lumbar lordosis mismatch (PI-LL), and C7 sagittal vertical axis (SVA) in which disability occurs based on an Oswestry Disability Index (ODI) of 40. However, the patients' age was not accounted for in determining these thresholds and ODI has been shown to vary with age. The objective was to determine new thresholds based on age. METHODS: This is a multicenter, prospective study of consecutive ASD patients. Inclusion criteria included: age >18 years and ASD. Patients were stratified into the following age groups: =45 years, 46 to 64, 65 to 74, =75. Multivariate linear regressions were conducted for baseline PT, PI-LL, and SVA with baseline ODI and age on all patients. Based on previous studies, an ODI of 40 was used as the threshold for disability. Individual patient thresholds were calculated based on their age. The thresholds were averaged across the age groups. RESULTS: Eight hundred thirty-three patients were included, (396 op, 437 nonop). Patients with only sagittal deformity for the age groups were the following: =45 (18.8%), 46 to 64 (19.4%), 65 to 74 (40.1%), =75 (50%). Age alone significantly predicted ODI (r 2 = 0.17, P < .0001). Regressions for PT (r 2 = 0.27, P < .0001), PI-LL (r 2 = 0.27, P < 0.0001, and SVA (r 2 = 0.32, P < .0001) including age were all predictive of ODI. Thresholds for the entire cohort were: PT = 21.9 ± 4.7 deg, PI-LL = 11.6 ± 7 deg, SVA = 6.7 ± 2.5 cm. Thresholds for the age groups were: PT (deg): =45 (15.3 ± 2.3), 46 to 64 (22.6 ± 1.5), 65 to 74 (26.2 ± 0.8), =75 (29.1 ± 0.8). PI-LL (deg): =45 (1.7 ± 3.5), 46 to 64 (12.5 ± 2.2), 65 to 74 (18 ± 1.2), =75 (22.4 ± 1.3). SVA (cm): =45 (3.3 ± 1.2), 46 to 64 (7.1 ± 0.8), 65 to 74 (9.0 ± 0.4), =75 (10.5 ± 0.4). CONCLUSION: Spinopelvic radiographic thresholds correlated to moderate to severe regional low back disability increase as patients age. These results suggest that preoperative surgery planning and patient counseling should consider patient age. Further study of Schwab SRS sagittal modifier correction goals for individual age groups is warranted.